Determining the efficiency of fast ultrahigh-density writing of low-conductivity patterns on semiconducting polymers - Keivanidis, Panagiotis E.; Di Donate, Andrea; Mencarelli, Davide; Esposito, Alessandro; Ye, Tengling; Lanzani, Guglielmo; Venanzoni, Giuseppe; Pietrangelo, Tiziana; Morini, Antonio; Farina, Marco (My University, 2015)
We present a nano-patterning process for semiconducting polymeric composites that could potentially be utilized for the development of polymer-based data storage devices. Nano-patterning (writing) operates on the basis of the mechanical interaction between the electrically unbiased tip of an atomic force microscope and the surface of polymeric composite films. Via friction forces, the tip/sample interaction produces a local increase of molecular disorder in the polymer matrix, inducing a localized lowering in the conductivity of the organic semiconductor. Herein we suggest a figure of merit for quantifying the efficiency of pattern formation and we address the dependence of the writing process on the thermal annealing temperature of the composite film. Control experiments on composite films deposited on substrates with different roughness suggest that the writing effect is invariant to the roughness of the substrate. The potential storage density of the writing process depends on the tip curvature.
Keywords: Semiconducting polymers; Composite films